PENGARUH PROFITABILITAS, INVESTMENT OPPORTUNITY SET (IOS), LIKUIDITAS DAN KEBIJAKAN DIVIDEN (Studi pada Perusahaan Sektor Consumer Goods di Bursa Efek Indonesia) - Hesty Erviani Zulaecha; Desrir Miftah (Universitas Muhammadiyah Tangerang, 2018)
The purpose of investment done by investors in the capital market is to getreturn of said investment. Expectations of investors in investing is to obtaindividend payout ratio. dividend payout ratio can be determined by analyzingthe company's financial performance which is proxied by Return on Assets,Sales Growth, Market to Book Value and Current Ratio. Companies classifiedin consumer goods sector selected as the population used in this study arelisted on the Stock Exchange 2013-2016 period. Purposive sampling is usedto get the sample in this research using criterias and 12 companies or 48firm-years are the samples. This research is using multiple linear regression.Based on the results of the partial test (t test) on the real level (α) = 5% canbe seen that the variablel return on assets have a significant and positiveimpact on dividen payout ratio, Sales Growth, Market to Book Value andCurrent Ratio have no significant effect on dividen payout ratio.